Influence of altitudes and development stages on the chemical composition and antioxidant capacity of Andean blackberries (Rubus glaucus Benth) - Guevara-Terán, Mabel; Tejera, Eduardo; Vásquez-Castillo, Wilson; Santos-Buelga, Celestino; González-Paramás, Ana M.; Alvarez-Suarez, José M. (Frontiers in Nutrition, 2024)
Background The Andean blackberry (Rubus glaucus Benth), locally known as “Mora de Castilla,” is a high-altitude fruit rich in phytochemicals, mainly anthocyanins, with potent antioxidant properties. Although its chemical composition has been studied, the influence of altitude on its phytochemical profile and antioxidant capacity is still unclear. This research aimed to investigate the effects of development stages and altitude on the phytochemical profile and antioxidant activity of this fruit. Methods Andean blackberry fruits were collected at different altitudes and development stages in the central Andean region of Ecuador. An hydroalcoholic extraction was used to quantify the compounds and determine the total antioxidant activity, while solid phase extraction (SPE) was performed to separate anthocyanins from other compounds. Ultra-high-performance liquid chromatography coupled to a triple quadrupole mass spectrometer (HPLC-DAD/ESI-MSn) was used to identify anthocyanin and non-anthocyanin phenols, while total antioxidant capacity, total polyphenols, total flavonoid content, and total anthocyanin content were quantified spectrophotometrically. Results Flavonols and anthocyanins constitute the majority of the flavonoids identified in the Andean blackberry extracts, both in terms of peak areas and number of identified compounds, followed by ellagic and gallic acid derivatives, as well as phenolic acids, mainly hydroxycinnamic acids. Quercetin was identified as the predominant flavonol in unripe berries, where anthocyanins were not significantly present. On the contrary, in ripe berries, cyanidin and its glycosides stood out as the main anthocyanins and predominant compounds. We observed that in the early stages of ripening, the total polyphenol content predominates in the berries and is mainly responsible for their antioxidant capacity. However, as the fruit ripens, the total anthocyanin content increases, becoming the most prominent bioactive compounds in fully ripe berries. Conclusion The results suggest that higher altitude environmental conditions may improve the composition, concentration of phenolic compounds, and antioxidant activity of Andean blackberries. Overall, our findings highlight the high functional value of this fruit, supporting its health-protective effects when consumed regularly, either as fresh fruit or in nutraceutical form.